Progressive changes in T(1), T(2) and left-ventricular histo-architecture in the fixed and embedded rat heart. - Hales, P; Burton, R; Bollensdorff, C; Mason, F; Bishop, M; Gavaghan, D; Kohl, P; Schneider, J (2010)
Chemical tissue fixation, followed by embedding in either agarose or Fomblin, is common practice in time-intensive MRI studies of ex vivo biological samples, and is required to prevent tissue autolysis and sample motion. However, the combined effect of fixation and sample embedding may alter tissue structure and MRI properties. We investigated the progressive changes in T(1) and T(2) relaxation times, and the arrangement of locally prevailing cardiomyocyte orientation determined using diffusion tensor imaging, in embedded ex vivo rat hearts fixed using Karnovsky's solution (glutaraldehyde-formaldehyde mix). Three embedding media were investigated: (i) standard agarose (n = 3 hearts); (ii) Fomblin (n = 4 hearts); and (iii) iso-osmotic agarose (n = 3 hearts); in the latter, the osmolarity of the fixative and embedding medium was adjusted to 300 mOsm to match more closely that of native tissue. The T(1) relaxation time in the myocardium showed a pronounced decrease over a 48-h period following embedding in Fomblin (-11.3 ± 6.2%; mean ± standard deviation), but was stable in standard agarose- and iso-osmotic agarose-embedded hearts. The mean myocardial T(2) relaxation time increased in all embedded hearts: by 35.1 ± 14.7% with standard agarose embedding, 13.1 ± 5.6% with Fomblin and 13.3 ± 1.4% with iso-osmotic agarose. Deviation in the orientation of the primary eigenvector of the diffusion tensor occurred in all hearts (mean angular changes of 6.6°, 3.2° and 1.9° per voxel after 48 h in agarose-, Fomblin- and iso-osmotic agarose-embedded hearts, respectively), indicative of progressive structural changes in myocardial histo-architecture, in spite of previous exposure to fast-acting tissue fixation. Our results suggest that progressive structural changes occur in chemically fixed myocardium, and that the extent of these changes is modulated by the embedding medium, and by osmotic gradients between the fixative in the tissue and the surrounding medium. Copyright © 2010 John Wiley and Sons, Ltd.